Posterior reversible encephalopathy syndrome: long-term follow-up. Issue 7 (1st December 2009) - Roth, Christian; Ferbert, Andreas
Abstract : Background: Posterior reversible encephalopathy syndrome (PRES) has been known for more than 10 years. The long-term prognosis of this condition remains unknown. Patients and methods: In 2006, the authors screened retrospectively the medical records of our department between 1993 and 2006 for PRES. The authors identified 13 patients. Since 2006, another 12 patients have been included prospectively. Since then, follow-up has been performed yearly for all patients. They were investigated in the outpatient clinic or, if they declined to attend, were interviewed by telephone. Results: The authors identified 25 patients with 27 episodes of PRES. Eighty-four per cent of the patients had generalised seizures. Their mean blood pressure was 167/100 mm Hg. Follow-up was performed for all patients over a mean period of 2250 days (range 59–9396; median 1699). Symptoms resolved, on average, after 7.5 days. Restitution of imaging abnormalities could be shown in 72% of cases. All others showed a clear improvement, but without complete restitution, after a mean duration of 41 days. Recurrence of PRES was observed in two patients (8%), 3 years after complete recovery from their first episode. Conclusion: These data show that PRES has a good short-term and long-term prognosis. Recurrence is infrequent, even though trigger factors for PRES were repeatedly experienced by the patients. Resolution of MRI lesions is slower than clinical recovery.